Analisis Karakteristik Parameter Hidrologi akibat Alih Fungsi Lahan di Daerah Sukoharjo melalui Citra Landsat Tahun 1997 dengan Tahun 2002 - Alif Noor Anna; Retno Woro Kaeks; Wahyuni Apri Astuti (Universitas Muhammadiyah Surakarta, 2010)
The Study, carried out Sukoharjo, deals with the effect of land function change from 1997 to 2002 toward the change of chosen hydrological parameters. The hydrological parameter constituses the coefficient runoff (C), the extra soil water (id), and the amount of constant stream (Wa). The process of land function the change is searched by using landsat image composit RGB (Red Green Blue) 452. Meanwhile, the aims of the study are (1) to determine the types and distribution for the process of land function change, and (2) to analyze the change of coefficient value runoff (C), the extra soil water (Id), and the amount of constant stream (Wa) within the area of research. The result of the study shown that there are many types of land function change, which occurred in almost all the area of research except the one type coming from the river becoming wet/dry rice field/residence/forest of which only occurred in Nguter sub district. The condition because of the straightening Bengawan Solo River in the sub district, cousequenly, the land function change proceses from the river into the land and vice versa. Moreover, of the 7 types of land function change in the area of research, the widest type of land function change covering the whole district is a change from forest/ horticulture/dry or wet rice field into residence. The effect of such a change has also caused a change in the characteristics of chosen hydrological parameter. Such a change can be seen from the value C, Id, and Wa. Furthermore, the change can be clarified as follow: the value C and Wa tend to rise while Id tends to decrease. This mean that the land function change has resulted in great abundant and decrease of water absorbed in the soil. In general, the availability of water source within the area can still be supplied from the seemingly increased constant stream. Such a condition might be caused by the ratio between the built land and the proportional open land of which about 30 % of the whole space.